High-performance work practices and labour productivity: a six wave longitudinal study of UK manufacturing and service SMEs - Sheehan, Maura; Garavan, Thomas (International journal of human resource management, 2022)
This study utilises both evolutionary resource-based view (EBRV) and open systems theory to investigate the long term impact of high-performance work practices (HPWPs) on labour productivity in UK manufacturing and service sector SMEs. We investigate both forward and reverse causality and the moderating role of owner-manager strategic orientation, and whether such relationships are influenced by firm size and age. Utilising a longitudinal data set (a balanced panel) comprising 284 UK SMEs and six waves of data collection over a ten-year time period (2007-2017), we found support for both forward and reverse causality. Prior investments in HPWPs were positively associated with subsequent firm labour productivity and prior labour productivity was positively associated with future investment in HPWPs. The size of the estimated coefficients for these relationships were consistently larger for small firms than for medium sized firms, however there were not significant for firm age. We additionally found that owner-manager strategic orientation towards HR moderated both forward and reverse causality relationships and that this relationship increased over time. The size of the estimated coefficients was larger in small firms compared to medium-sized firms. Overall, our findings support calls to investigate both forward and reverse causality and to better understand potential differences between small and medium sized firms.